The development of the Postdoctoral Nurses Competence Scale: A Delphi consensus and content validity study - Sterkenburg, Annika; van Dongen, Lisa J. C.; Hafsteinsdottir, Thora B. (Elsevier BV, 2025)
Background: PhD prepared nurses advance nursing science through research and integration of findings into practice. They demonstrate expertise in research, education, patient care, and policy. Various professional competencies are required for success in research, clinical practice, and education. Assessment of professional competencies is expected to stimulate competence and career development.
Aim: To reach consensus on professional competencies, develop an instrument to measure professional competencies of PhD prepared nurses and assess the content validity of the instrument.
Method: A Delphi consensus and content validity study was conducted using online questionnaires completed by international PhD prepared nurse researchers. The relevance of and agreement with the competencies were measures using Likert-scales and open-ended questions to determine consensus. The Postdoctoral Nurses Competence Scale was developed, and its content validity evaluated.
Results: Initially, four of 15 competencies were deemed 'very' or 'fairly' important by 18 PhD prepared nurses. In the second round with 13 adjusted competencies, eight competencies were rated 'very' or 'fairly' important. The content validity index scored 0.91.
Conclusion: Consensus was reached on most professional competencies, and the 13-item self-assessment instrument demonstrated excellent content validity. Further research is recommended to evaluate additional clinimetric properties before use of the instrument.